Correlation of telomere length and DNA damage markers with severity and associated depressive states in patients with OSAS - Jiang, Yu; Qu, Meixin; Cheng, Feng; Sun, Huifen; Dai, Jie; Wu, Zhen (Frontiers in Neurology, 2025)
ObjectiveInvestigation of the correlation of peripheral blood leukocyte relative telomere length (RTL) and DNA damage markers with severity and related depressive states in patients with obstructive sleep apnea syndrome (OSAS).MethodsA total of 110 OSAS patients admitted to the hospital between January 2023 and December 2024 were selected. Based on examination results, the OSAS patients were divided into the mild to moderate and the severe groups. Additionally, 45 healthy volunteers who voluntarily participated in the study during the same period were included as a healthy control group. RTL and DNA damage markers [phosphorylated histone H2AX (γH2AX), 8-hydroxydeoxyguanosine (8-OHdG)] of the three groups were compared among the three groups. The Hamilton Depression Scale (HAMD) was used to assess the depressive status of OSAS patients, who were further categorized into the depressed group (HAMD score >7) and non-depressed group (HAMD score ≤7) based on the severity of depression. The correlation of RTL and the above markers with the severity of the disease of OSAS patients and their HAMD scores was analyzed by Pearson correlation analysis, with the efficacy of RTL and DNA damage markers in predicting secondary depression in OSAS patients analyzed by plotting the receiver operating characteristic curve (ROC).ResultsThe RTL values of patients in the severe and the mild to moderate group were significantly lower than those of the healthy control group with higher levels of γH2AX and 8-OHdG, and the differences of three indexes between the severe group and the mild to moderate group registered statistical significance (p < 0.05). Pearson analysis showed that RTL was negatively correlated with the HAMD scores of patients with OSAS (r1 value = −0.65); γH2AX and 8-OHdG were positively correlated with the HAMD scores of OSAS patients (r2 value = 0.62, r3 value = 0.65, both p < 0.05). ROC analysis based on RTL and DNA damage markers found that the area under the curve (AUC) values of RTL, γH2AX, and 8-OHdG for predicting secondary depression in OSAS patients were 0.665, 0.865, and 0.752, respectively.ConclusionRTL, γH2AX, and 8-OHdG exert an important role in assessing the severity of disease in OSAS patients. Besides, there exists a significant correlation between the three indexes and the depressive state of patients, boasting a good predictive efficacy for their secondary depression.